Papua New Guinea Government, Economy and Society - Howes, Stephen; Pillai, Lekshmi N. (Pacific Series, 2022)
Papua New Guinea (PNG), a nation of now almost nine million people, continues to evolve and adapt. While there is no shortage of recent data and research on PNG, the two most recent social science volumes on the country were both written more than a decade ago. Since then, much has changed and much has been learnt. What has been missing is a volume that brings together the most recent research and reports on the most recent data. Papua New Guinea: Government, Economy and Society fills that gap. Written by experts at the University of Papua New Guinea and The Australian National University among others, this book provides up-to-date surveys of critical policy issues for PNG across a range of fields, from elections and politics, decentralisation, and crime and corruption, to PNG's economic trajectory and household living standards, to uneven development, communication and the media. The volume's authors provide an overview of the data collected and research undertaken in these various fields in an engaging and accessible way. Edited by Professor Stephen Howes and Professor Lekshmi N. Pillai, Papua New Guinea: Government, Economy and Societyis a must-read for students, policymakers and anyone interested in understanding this complex and fascinating country.